Accreditation and re-accreditation from the National University (Costa Rica): two experiences of continuous improvement - González Sandoval, Elizabeth (2012)
The accreditation of courses at the National University (UNA) has become one of the mechanisms for quality management in the context of continuous improvement of formal university education. In this sense, it addresses the experience of two races that have been accredited and subsequently reacreditadas. It exposes the race experience in Information Systems Engineering and Mathematics Teaching career, both belonging to academic units of the College of Natural Sciences. We report the distance traveled since the first self-assessment process to reaccreditation, highlighting the achievements made ​​improvement, to improve aspects that remain, or those arising as a result of the second self-assessment process.